Application of high degree of polymerization high deacetylation chitosan in anti-HPV16 / 18 mucosal repair hydrogel

CN122954810APending Publication Date: 2026-10-23JINAN NUOZHIYUAN BIOTECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611073071.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-20
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

针对现有技术的不足,本发明提供了一种高聚合度高脱乙酰壳聚糖在抗HPV16/18黏膜修复水凝胶中的应用,具备HPV16/18体外高效阻隔、宫颈上皮创面快速修复及维持阴道乳酸杆菌优势菌群,且工艺标准化,能稳定进行工业化放大生产的优点,解决了现有多糖制剂因分子参数宽泛导致抗病毒活性不足、常温制备破坏多糖活性、pH体系刺激宫颈创面、黏膜黏附时间短、无法同步修复黏膜与调节阴道微生态、量产成本高及批次稳定性差的缺陷

Benefits of technology

1、本发明通过精准调控壳聚糖分子双参数,最大化游离氨基活性,细胞模型下对HPV16/18假病毒阻隔效率接近完全阻断,性能显著优于普通葡聚糖及偏离参数区间的氨基多糖凝胶;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122954810A_ABST
    Figure CN122954810A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of medical biological polysaccharide external preparations, and discloses application of high-polymerization-degree high-deacetylation chitosan in an anti-HPV16 / 18 mucosa repair hydrogel, wherein the high-polymerization-degree high-deacetylation chitosan is used as a core active component in preparation of a cervical mucosa repair hydrogel for HPV16 / 18 high-risk subtypes by limiting specific polymerization degree and deacetylation degree intervals; meanwhile, the chitosan quaternary ammonium salt, sodium alginate, panthenol, sodium hyaluronate, lactic acid buffer and sterile purified water are compounded to prepare the hydrogel, the prepared hydrogel has a pH value range of 4.0-5.0, a viscosity of 15000-20000 mPa.s, and a mucosa adhesion duration of the hydrogel of greater than or equal to 7 hours; in addition, the high-polymerization-degree high-deacetylation chitosan can also be used for preparing an HPV high-risk infection intervention external preparation, a cervical wound repair mucosa dressing, a vaginal microecological regulation gel and a gynecological medical external gel.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of medical biological polysaccharide topical preparation technology, specifically the application of a highly polymerized, highly deacetylated chitosan in an anti-HPV16 / 18 mucosal repair hydrogel. Background Technology

[0002] Human papillomavirus (HPV) is an epitheliotropic double-stranded DNA virus, with over 150 subtypes identified to date. Persistent infection with the two high-risk subtypes, HPV16 and HPV18, is a major cause of cervical intraepithelial neoplasia (CIN) and cervical cancer. Epidemiological data shows that approximately 70% of cervical malignancies worldwide are closely related to these two types of viruses. Current HPV vaccines only provide preventative protection and cannot eliminate existing viral infections. Clinically, there is still a lack of safe, long-acting topical formulations that can effectively block the virus while also repairing the vaginal mucosa and protecting the vaginal flora.

[0003] Existing topical anti-HPV gynecological products are mainly divided into three categories, but all have inherent drawbacks that cannot be overcome: Category 1, interferon protein preparations, whose active ingredient is protein, have poor chemical stability in aqueous solution, short half-life in vivo, and require high-frequency administration; long-term continuous use can easily induce adaptive mutations in HPV; and the preparation itself is irritating to the mucosa, which can disrupt the dominant vaginal lactobacillus flora and increase the risk of secondary bacterial vaginosis. Category 2, active peptide anti-HPV preparations, among which the separation and purification process of peptide raw materials is complex, the cost of large-scale production is high, and mass production is difficult; in addition, peptides have strict storage conditions and short shelf life at room temperature, which limits their end-use applications. Category 3, common polysaccharide gynecological gels (chitosan / dextran-based), broadly use only common chitosan, oligochitosan, or high molecular weight dextran in the industry, without precisely defining the narrow range of molecular polymerization and deacetylation degrees. This results in significantly insufficient ability to block viruses in vitro and repair epithelial wounds. Therefore, simply increasing viscosity to prolong retention time easily hinders vaginal secretion circulation, leading to low repair efficiency of damaged cervical mucosa and a high clinical recurrence rate. Furthermore, conventional room-temperature stirring preparation processes cause chitosan amino degradation, resulting in continuous decline in activity. In addition, the pH system has poor matching, either being too acidic and irritating eroded wounds, or too alkaline and disrupting the weakly acidic vaginal microecology. Moreover, the formula has a single function, only able to inhibit bacteria or moisturize, and cannot simultaneously achieve the triple functions of efficient HPV blocking, mucosal repair, and regulation of bacterial homeostasis.

[0004] Existing literature and patents only vaguely describe chitosan as having weak in vitro anti-HPV activity, but fail to disclose the specific narrow parameter range of 80–100 degree of polymerization and 92%–95% degree of deacetylation, and further fail to verify the strong correlation between these molecular parameters and viral blocking and cell repair effects. There is an urgent need in this field for a medical mucosal repair hydrogel with precisely controllable molecular parameters, synergistic formulation effects, a supporting low-temperature aseptic protection process, and stable industrial mass production capability. Summary of the Invention

[0005] (a) Technical problems to be solved To address the shortcomings of existing technologies, this invention provides an application of highly polymerized, deacetylated chitosan in anti-HPV16 / 18 mucosal repair hydrogels. This hydrogel offers advantages such as highly effective in vitro blocking of HPV16 / 18, rapid repair of cervical epithelial wounds, and maintenance of the dominant vaginal lactobacillus flora. Furthermore, the standardized process allows for stable industrial-scale production. This invention overcomes the shortcomings of existing polysaccharide preparations, including insufficient antiviral activity due to broad molecular parameters, destruction of polysaccharide activity during room temperature preparation, cervical wound irritation due to pH levels, short mucosal adhesion time, inability to simultaneously repair the mucosa and regulate the vaginal microecology, high production costs, and poor batch stability.

[0006] (II) Technical Solution To achieve the above objectives, the present invention provides the following technical solution: the application of a high degree of polymerization and high degree of deacetylation chitosan in anti-HPV16 / 18 mucosal repair hydrogel, wherein the high degree of polymerization of the high degree of polymerization and high degree of deacetylation chitosan is 88-95 and the degree of deacetylation is 93%-94%.

[0007] Preferably, the high-polymerization-degree-of-deacetylation chitosan is used not only to prepare anti-HPV16 / 18 mucosal repair hydrogels, but also to prepare topical intervention preparations for high-risk HPV16 / 18 infections, cervical mucosal repair dressings, vaginal microecological regulation hydrogels, and topical preparations for gynecological wound repair.

[0008] Preferably, the anti-HPV16 / 18 mucosal repair hydrogel is composed of the following raw materials in parts by weight: 5.0-6.5 parts of high-polymerization-degree-of-polymerization-high-deacetylation chitosan; 2.2-2.8 parts of chitosan quaternary ammonium salt; 1.8-2.3 parts of sodium alginate; 3.0-4.0 parts of panthenol; 1.5-2.0 parts of sodium hyaluronate; 0.8-1.2 parts of lactic acid buffer; and sterile purified water to make up to 100 parts.

[0009] Preferably, the preparation method of the mucosal repair hydrogel includes the following steps: Step 1: Weigh the raw materials and perform dry heat removal pretreatment; Step 2: Dissolve the highly active chitosan at low temperature, and then remove impurities by 0.22μm ultrafiltration; Step 3: Prepare the polysaccharide matrix by stepwise cross-linking at room temperature; Step 4: Mix the active ingredients with the moisturizing components; Step 5: Precisely adjust the pH of the mixture and mix at a low temperature; Step 6: The low-temperature mixing system is aseptically filtered and filled using ISO5 laminar flow in a graded clean area.

[0010] Preferably, in step one, all raw materials are accurately weighed according to their weight proportions; the solid polysaccharide raw materials are then placed in an electric heating drying oven and dried at 120°C for 30 minutes to remove endotoxins; panthenol, sodium hyaluronate, lactic acid buffer, and other liquid excipients are pre-filtered through a 0.45μm PTFE filter membrane for later use; the production equipment is pre-cleaned with water for injection and sterilized with pure steam.

[0011] Preferably, in step two, highly active chitosan is added to 20 to 50 times its mass of sterile purified water to prepare an aqueous solution with a mass fraction of 2% to 5%; the solution is stirred at low temperature and in the dark at 4 to 10°C and 70 to 80 r / min until completely dissolved; and protein impurities are removed by low-temperature circulating filtration using a 0.22 μm ultrafiltration membrane.

[0012] Preferably, the step-by-step cross-linking process for preparing the polysaccharide matrix at room temperature in step three is as follows: (1) Add chitosan quaternary ammonium salt to pre-stored sterile purified water and stir at 200-300 r / min to swell for 20-30 min to form a transparent cationic colloid; (2) Add sodium alginate into the system slowly and evenly in 3 to 5 batches, and stir at the same speed for 25 to 35 minutes to form a three-dimensional slow-release network skeleton; (3) After cross-linking, the mixture is sealed and left to stand for 10-15 minutes for vacuum degassing to obtain the polysaccharide matrix.

[0013] Preferably, in step four, the mixing process of the moisturizing components involves sequentially and uniformly adding chitosan active solution, panthenol, and sodium hyaluronate to the polysaccharide matrix; and stirring at a uniform speed of 300 r / min for 40 min at room temperature.

[0014] Preferably, the pH precise adjustment + low-temperature mixing process in step five is as follows: (1) Add lactic acid buffer dropwise under low speed stirring at 100-200 r / min, monitor pH online in real time, and keep it stable at 4.0-5.0; (2) Low temperature mixing: temperature 6~8℃.

[0015] Preferably, the aseptic filtration and ISO5 laminar flow filling process in the graded clean area in step six is ​​as follows: (1) The mixed gel material was filtered through a 0.22μm sterile terminal filter membrane; (2) The filtered material is transferred to a Class B clean production room through a closed pipeline and aseptic filling and sealing are completed in an ISO5 unidirectional laminar flow hood. (3) Monitoring of settling bacteria, airborne bacteria, and surface microorganisms is carried out simultaneously throughout the entire production process; simulated filling of culture medium is performed for each batch; (4) After sealing, the finished product should be stored in a light-proof, sealed warehouse at 4-25℃; The finished product's physicochemical properties are as follows: dynamic viscosity 17000~18000mPa·s; in vitro mucosal adhesion time ≥8h; pH value: 4.0~5.0.

[0016] Compared with the prior art, the present invention provides an application of highly polymerized, highly deacetylated chitosan in anti-HPV16 / 18 mucosal repair hydrogels, which has the following beneficial effects: 1. This invention maximizes the activity of free amino groups by precisely controlling the two parameters of chitosan molecules. In a cell model, the blocking efficiency against HPV16 / 18 pseudoviruses is close to complete, and the performance is significantly better than that of ordinary dextran and amino polysaccharide gels that deviate from the parameter range. 2. This invention promotes the proliferation and migration of cervical epithelial cells through the synergistic effect of multi-component compounding, and can effectively repair virus-induced cervical erosion and mucosal damage. 3. This invention achieves low mucosal irritation by matching the pH of the gel to the tolerance range of damaged cervical mucosa; it can selectively inhibit harmful pathogenic bacteria in the vagina, protect the dominant lactobacillus flora, and reduce the probability of secondary infection; it plays a virus blocking role by relying on the physical space occupation mechanism, and will not induce adaptive infection mutations in HPV, supporting long-term continuous use. Its viscosity range is reasonably designed, and the gel adheres to the cervical mucosa for ≥7 hours, with slow and sustained release of active components, extending the action period of a single administration. 4. This invention uses all commercially available medical-grade standardized products as raw materials, resulting in low procurement costs; the entire preparation process uses industry-standard and mature equipment, with standardized and controllable operation, making it suitable for large-scale mass production, and the overall production cost is far lower than that of interferon and active polypeptide gynecological preparations. 5. This invention preserves the bioactivity of polysaccharides to the greatest extent through a low-temperature, low-pressure, multi-stage sterilization and filtration process throughout the entire process; and through supporting GMP control measures such as dry heat pyrogen removal, environmental microbial monitoring, and culture medium simulation filling, the final product meets the national standards for medical gynecological gels in terms of sterility, endotoxin, microbial limits, and physicochemical stability. Attached Figure Description

[0017] Figure 1 This is a flowchart illustrating the preparation process of the repair hydrogel according to the present invention. Detailed Implementation

[0018] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0019] Please see Figure 1 The application of a high-polymerization-degree, high-deacetylated chitosan in anti-HPV16 / 18 mucosal repair hydrogel is disclosed. The raw material is defined as follows: high-polymerization-degree, high-deacetylated chitosan with a polymerization degree of 80–100 and a deacetylation degree of 92%–95%; preferably, the polymerization degree is 88–95 and the deacetylation degree is 93%–94%. Within this molecular range, the free amino group density and polymer spatial configuration of chitosan synergistically match the electrostatic binding sites of HPV16 / 18 L1 capsid proteins, blocking viral adsorption and invasion of cervical epithelial cells through spatial occupancy. Simultaneously, it can regulate fibroblast proliferation and migration pathways, accelerating the healing of damaged mucosa. Besides being used to prepare anti-HPV16 / 18 mucosal repair hydrogel, this chitosan can also be used to prepare topical intervention agents for high-risk HPV16 / 18 infections, cervical mucosal repair dressings, vaginal microecological regulation hydrogels, and topical preparations for gynecological wound repair.

[0020] The standardized formulation of the repair hydrogel (parts by weight, bring sterile purified water to 100 parts) is as follows: Table 1 ; The physicochemical properties of the repair hydrogel product (with corresponding national standard testing methods) are as follows: (1) Dynamic viscosity (25℃, rotational viscometer GB / T10247): 15000~20000mPa·s; preferably 17000~18000mPa·s; (2) Duration of in vitro mucosal adhesion (pig cervical mucosal simulation test): ≥7h; preferably ≥8h; (3) pH value (acidity meter GB / T9724): 4.0~5.0; The physiological pH of a healthy vagina is 3.8–4.5, and the tolerance range for acid and alkaline conditions such as cervical erosion and damaged mucosa is even wider. This lactic acid buffer system maintains a stable pH of 4.0–5.0, avoiding the stimulation of damaged wounds by a highly acidic environment while not inhibiting the proliferation of lactobacilli, thus balancing wound tolerance and vaginal microecological balance.

[0021] Industrial GMP aseptic preparation process: Step 1: The production equipment is pre-cleaned with water for injection and sterilized with pure steam; Step 2: Temperature is controlled throughout the process to avoid degradation of polysaccharide amino groups and to fully preserve biological activity; Step 3: A bubble-free, homogeneous, and stable polysaccharide matrix is ​​obtained; Step 4: The endpoint of stirring is determined by the following criteria: no stratification, no water separation, and no visible particles; Step 5: The colloidal microstructure is refined under low-temperature mixing to improve mucosal adhesion and the uniformity of sustained release of active components; Step 6: Each batch of culture medium is simulated and filled to verify aseptic assurance capability, and the products are stored in a light-proof, sealed warehouse to avoid high temperatures and direct sunlight.

[0022] The entire process is equipped with mass production equipment including: a low-temperature stirred reactor, an ultrafiltration system, a vacuum degassing tank, a 0.22μm sterilization filtration system, a Class B cleanroom, and a Class A laminar flow filling line. All of these are mature, commonly used equipment in the medical gel industry, requiring no customized special equipment. Pilot-scale production at batches of 50kg and 500kg can be completely reproduced.

[0023] Mechanism of action of each raw material: (1) High degree of polymerization and high deacetylation chitosan (core active ingredient): Free amino groups electrostatically bind to HPV16 / 18L1 capsid protein, blocking the virus adsorption to epithelial cells in an in vitro cell model; regulating the proliferation and migration of epithelial fibroblasts, and accelerating the healing of cervical wounds. (2) Chitosan quaternary ammonium salt: inhibits vaginal opportunistic pathogens such as Gardnerella vaginalis and anaerobic bacteria, protects the dominant lactobacillus flora; enhances the adhesion properties of gel mucosa and helps capture free virus particles; (3) Sodium alginate: cross-links with cationic polysaccharides to form a three-dimensional sustained-release framework, which can controllably release active components and prolong the duration of mucosal action; (4) Panthenol: It penetrates the superficial epithelial tissue, moisturizes and repairs damaged mucous membranes, and relieves the stinging, dryness and discomfort caused by drug administration; (5) Sodium hyaluronate: forms a hydrophilic and moisturizing protective film on the mucosal surface, reduces instrument friction damage, and works synergistically with panthenol to rebuild the physical barrier of the mucosa; (6) Lactic acid buffer: It locks in the pH of the system for a long time, weakens the irritation of the gel, and maintains the weakly acidic microecological environment of the vagina; (7) Sterile purified water: The solvent dispersion medium adopts the purification standard of water for injection and is treated with sterilization and pyrogen removal.

[0024] The core innovation of this invention compared to existing technologies (1) Pioneering narrow-range molecular parameter synergistic limitation: Existing technologies only broadly select low degree of polymerization (<60) or ultra-high degree of polymerization (>120) chitosan, without any comparative documents simultaneously limiting the degree of polymerization to 80-100 and the degree of deacetylation to 92%-95%; This invention has confirmed through multi-gradient control experiments that only this range can simultaneously achieve efficient HPV blocking and mucosal repair.

[0025] (2) The six-component synergistic compound system produces unexpected synergistic effects: chitosan with single limited parameters has weak adhesion and poor sustained release; chitosan quaternary ammonium salt or sodium alginate alone has no strong anti-HPV ability; each component alone has only a single function, but after compounding, it can achieve the triple function of virus blocking, wound repair and microbial regulation, which is a typical creative situation of the composition.

[0026] (3) The matching low-temperature sterile activity protection process is a targeted innovation: Existing polysaccharide gels are all prepared at room temperature, which leads to high-temperature degradation of polysaccharide amino groups and a significant decrease in antiviral activity; the complete set of low-temperature dissolution, low-temperature ultrafiltration and low-temperature mixing processes of this invention are specially adapted to this high-activity chitosan, and fully preserve the amino activity.

[0027] (4) The three physicochemical indicators of viscosity, adhesion time and pH are linked and matched: the existing technology only limits viscosity or pH alone, and does not coordinate the three indicators to fit the chitosan system; the combination of the three achieves the comprehensive effect of long-term sustained release, low irritation and suitability for cervical wounds.

[0028] The performance comparison between products prepared by the low-temperature process of this invention and those prepared by conventional room-temperature processes is as follows: Table 2 ; The above results show that the product prepared by the low-temperature process of the present invention is significantly better than the product prepared by the conventional room-temperature process in terms of key indicators such as dynamic viscosity, HPV blocking rate and chitosan amino retention rate (P<0.05 or P<0.01), which proves the necessity of the low-temperature process for protecting the activity of chitosan amino groups and maintaining the antiviral efficacy of the product.

[0029] Example 1 (Preferred Example) Raw material formulation: 6.0 parts of high-polymerization, high-deacetylated chitosan (polymerization degree 90, deacetylation degree 94%); 2.5 parts of chitosan quaternary ammonium salt; 2.0 parts of sodium alginate; 3.5 parts of panthenol; 1.8 parts of sodium hyaluronate; 1.0 part of lactic acid buffer; sterile purified water to a total of 100 parts. Preparation process: Prepared according to the process steps of this invention.

[0030] Example 2 (Boundary Value Verification – Lower Limit of Degree of Polymerization / Lower Limit of Degree of Deacetylation) Raw material formulation: 5.5 parts of high-polymerization, high-deacetylated chitosan (degree of polymerization 80, degree of deacetylation 92%); 2.2 parts of chitosan quaternary ammonium salt; 1.8 parts of sodium alginate; 3.0 parts of panthenol; 1.5 parts of sodium hyaluronate; 0.8 parts of lactic acid buffer; sterile purified water to a total of 100 parts. Preparation process: Prepared according to the process steps of this invention.

[0031] Example 3 (Boundary Value Verification - Upper Limit of Degree of Polymerization / Upper Limit of Degree of Deacetylation) Raw material formulation: 6.5 parts of high-polymerization-degree, high-deacetylated chitosan (degree of polymerization 100, degree of deacetylation 95%); 2.8 parts of chitosan quaternary ammonium salt; 2.3 parts of sodium alginate; 4.0 parts of panthenol; 2.0 parts of sodium hyaluronate; 1.2 parts of lactic acid buffer; sterile purified water to a total of 100 parts. Preparation process: Prepared according to the preparation process steps of this invention.

[0032] Example 4 (Intermediate Value Verification) Raw material formulation: 5.8 parts of high-polymerization, high-deacetylated chitosan (degree of polymerization 85, degree of deacetylation 93%); 2.5 parts of chitosan quaternary ammonium salt; 2.0 parts of sodium alginate; 3.5 parts of panthenol; 1.8 parts of sodium hyaluronate; 1.0 part of lactic acid buffer; sterile purified water to a total of 100 parts. Preparation process: Prepared according to the process steps of this invention.

[0033] Example 5 (Intermediate Value Verification) Raw material formulation: 6.2 parts of high-polymerization, high-deacetylated chitosan (polymerization degree 95%, deacetylation degree 95%); 2.5 parts of chitosan quaternary ammonium salt; 2.0 parts of sodium alginate; 3.5 parts of panthenol; 1.8 parts of sodium hyaluronate; 1.0 part of lactic acid buffer; sterile purified water to a total of 100 parts. Preparation process: Prepared according to the process steps of this invention.

[0034] Comparative Example 1 (Raw Material Substitution) 6.0 parts of ordinary dextran (degree of polymerization 120, degree of deacetylation 85%), the rest are the same as in Example 1.

[0035] Comparative Example 2 (parameters deviate significantly from the lower limit) 6.0 parts of low-parameter chitosan (degree of polymerization 60, degree of deacetylation 88%), the rest are the same as in Example 1.

[0036] Comparative Example 3 (parameters significantly deviate from the upper limit) 6.0 parts of superrange chitosan (degree of polymerization 110, degree of deacetylation 96%), the rest are the same as in Example 1.

[0037] Comparative Example 4 (parameters slightly lower than the lower limit of the wide range of this invention—degree of polymerization 75 / degree of deacetylation 90%) Raw material formulation: 6.0 parts of high-polymerization-degree, high-deacetylated chitosan (degree of polymerization 75, degree of deacetylation 90%); the remaining components are the same as in Example 1. Preparation process: Prepared according to the process steps described in Example 1.

[0038] Comparative Example 5 (parameters slightly higher than the upper limit of the wide range of this invention—degree of polymerization 105 / degree of deacetylation 96%) Raw material formulation: 6.0 parts of high-polymerization-degree, high-deacetylated chitosan (degree of polymerization 105, degree of deacetylation 96%); the remaining components are the same as in Example 1. Preparation process: Prepared according to the process steps described in Example 1.

[0039] Blank control group Remove the highly polymerized, highly deacetylated chitosan; otherwise, it is the same as in Example 1.

[0040] The split-component experimental group (verification of synergistic effect) To verify whether the six-component compound system of this invention has a synergistic effect, the following decomposition experiments were conducted (each decomposition experimental group was prepared according to the process steps of this invention): Experimental Group 1 (Core Chitosan Only): 6.0 parts of high-polymerization, high-deacetylated chitosan (polymerization degree 90, deacetylation degree 94%); sterile purified water to bring the total to 100 parts. Contains no chitosan quaternary ammonium salt, sodium alginate, panthenol, sodium hyaluronate, or lactic acid buffer.

[0041] Experimental Group 2 (Chitosan Quaternary Ammonium Salt + Sodium Alginate Only): 2.5 parts chitosan quaternary ammonium salt; 2.0 parts sodium alginate; sterile purified water to a total of 100 parts. Contains no high-polymerization, high-deacetylated chitosan, panthenol, sodium hyaluronate, or lactic acid buffer.

[0042] Experimental group 3 (excluding chitosan quaternary ammonium salt): 6.0 parts of high-polymerization-degree-of-polymerization-high-deacetylation chitosan; 2.0 parts of sodium alginate; 3.5 parts of panthenol; 1.8 parts of sodium hyaluronate; 1.0 part of lactic acid buffer; and sterile purified water to make up to 100 parts.

[0043] Experimental group 4 (excluding sodium alginate): 6.0 parts of high-polymerization, high-deacetylated chitosan; 2.5 parts of chitosan quaternary ammonium salt; 3.5 parts of panthenol; 1.8 parts of sodium hyaluronate; 1.0 part of lactic acid buffer; and sterile purified water to make up to 100 parts.

[0044] Experimental Example (I) Comparative Experiment of HPV Blocking Effect and Mucosal Repair Effect The test results are as follows: Table 3 Comparison of HPV blocking and mucosal repair effects of different formulations ; Note: Data are expressed as mean ± standard deviation, n=3.

[0045] (II) Decomposed Formulation Experiment (Synergistic Effect Verification): To verify whether the six-component compound system of the present invention has a synergistic effect, the HPV16 blocking rate, HPV18 blocking rate, and mucosal wound healing rate of the complete formula (Example 1) and each decomposed formulation experimental group were compared. The results are as follows: Table 4 Comparison of the effects of the split-square experiment ; Analysis of efficacy: Taking HPV16 blocking rate as an example, the blocking rate of the split-formula experimental group 1 (core chitosan only) was 78.5%, and the blocking rate of the split-formula experimental group 2 (quaternary ammonium salt + sodium alginate only) was 25.3%. The expected value of the simple sum of the two was approximately 103.8% (upper limit taken as 100%). The actual HPV16 blocking rate of the complete formula (Example 1) reached 99.9%, which, although affected by the upper limit of the percentage, was significantly higher than that of the split-formula experimental group 3 (without quaternary ammonium salt, 85.6%) and the split-formula experimental group 4 (without sodium alginate, 88.2%) (P < 0.01). This result indicates that although chitosan quaternary ammonium salt and sodium alginate do not have strong anti-HPV ability on their own, they can produce significant synergistic effects with the core chitosan in the complete formula, greatly improving the overall blocking effect. Similarly, in terms of mucosal wound healing rate, the complete formula (99.9%) was also significantly better than all the split-formula experimental groups (P < 0.01). The above-mentioned decomposition experiments fully demonstrate that the overall effect of the six-component compound system of the present invention is significantly better than the simple sum of the individual effects of each component, and there is a clear synergistic effect of "1+1>2" among the components.

[0046] (III) Mechanism Verification Experiment To further verify the mechanism by which highly polymerized, deacetylated chitosan blocks HPV viruses through electrostatic binding in this invention, the following characterization experiments were conducted: (1) Zeta potential analysis: The Zeta potentials of the high-polymerization-degree-of-polymerization-high-deacetylated chitosan solution (polymerization degree 90, deacetylation degree 94%) of the present invention, the low-parameter chitosan solution (polymerization degree 60, deacetylation degree 88%) of Comparative Example 2, and the ultra-range chitosan solution (polymerization degree 110, deacetylation degree 96%) of Comparative Example 3 were measured respectively. The results showed that the Zeta potential of the chitosan solution of the present invention was +42.3±2.1mV, which was significantly higher than +18.6±1.8mV of Comparative Example 2 (P<0.01) and +35.2±2.3mV of Comparative Example 3 (P<0.05). The higher positive charge density is conducive to strong electrostatic binding with the negatively charged HPV viral capsid protein, thereby effectively blocking the adsorption and invasion of the virus into the host cell.

[0047] (2) Scanning electron microscopy (SEM) observation: After co-incubating the hydrogel of the present invention (Example 1) with HPV16 pseudovirus particles, the aggregation state of the virus particles was observed using scanning electron microscopy. The results showed that the hydrogel of the present invention can effectively capture and aggregate HPV16 virus particles, forming obvious virus-gel aggregates. The virus particles are encapsulated in the three-dimensional network structure of the gel, thereby blocking the contact between the virus and cervical epithelial cells. In contrast, no obvious virus aggregation was observed in the gel of the blank control group.

[0048] The above-mentioned mechanism verification experiments have transformed the mechanism by which chitosan blocks viruses through "electrostatic binding" in this invention from theoretical speculation to empirical data, greatly enhancing the persuasiveness of the technical solution.

[0049] Based on the above experimental results: (1) When the degree of polymerization and degree of deacetylation of chitosan fall within the preferred range of 80-100 and 92%-95% (Examples 2 and 3), the gel has a very high in vitro blocking effect against HPV16 / 18 pseudoviruses (HPV16 blocking rate ≥99.3%, HPV18 blocking rate ≥99.0%), and excellent cervical epithelial wound healing ability (≥98.5%). When the molecular parameters fall within the boundaries of the wide range of 75-105 and 90%-96% of the present invention (Comparative Examples 4 and 5), although the various indicators are still significantly better than the existing technology products, a downward trend has begun to appear, proving that 80-100 and 92%-95% are more preferred parameter ranges. When the molecular parameters deviate significantly from this range (Comparative Examples 1-3), the effect decreases significantly (P<0.05).

[0050] (2) The decomposed experiment confirmed that the six-component compound system of the present invention has a significant synergistic effect. The HPV16 blocking rate of the complete formula (99.9%) is significantly better than that of each decomposed experimental group (P<0.01), which proves that there is a synergistic effect of "1+1>2" among the components.

[0051] (3) Zeta potential analysis and scanning electron microscopy observation empirically verified the mechanism by which highly polymerized, deacetylated chitosan binds HPV virus particles electrostatically through high positive charge density and encapsulates and aggregates the virus through a three-dimensional network structure.

[0052] The HPV blocking rate of the gel of this invention is significantly better than that of existing products, and it also has excellent mucosal repair function, achieving the dual effects of virus blocking and tissue repair.

[0053] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. The application of a high-polymerization-degree, high-deacetylated chitosan in an anti-HPV16 / 18 mucosal repair hydrogel, characterized in that, The high degree of polymerization and high degree of deacetylation of the chitosan is 80-100 and has a degree of deacetylation of 92%-95%.

2. The application of a high-polymerization-degree, high-deacetylation chitosan according to claim 1 in an anti-HPV16 / 18 mucosal repair hydrogel, characterized in that, The highly polymerized, deacetylated chitosan is used not only to prepare anti-HPV16 / 18 mucosal repair hydrogels, but also to prepare topical intervention agents for high-risk HPV16 / 18 infections, cervical mucosal repair dressings, vaginal microecological regulation hydrogels, and topical preparations for gynecological wound repair.

3. The application of a high-polymerization-degree, high-deacetylated chitosan according to claim 1 in an anti-HPV16 / 18 mucosal repair hydrogel, characterized in that, The anti-HPV16 / 18 mucosal repair hydrogel is composed of the following raw materials in parts by weight: 5.0-6.5 parts of high-polymerization, high-deacetylated chitosan; 2.2-2.8 parts of chitosan quaternary ammonium salt; 1.8-2.3 parts of sodium alginate; 3.0-4.0 parts of panthenol; 1.5-2.0 parts of sodium hyaluronate; 0.8-1.2 parts of lactic acid buffer; and sterile purified water to a total of 100 parts.

4. The application of a high-polymerization-degree, high-deacetylated chitosan according to claim 1 in an anti-HPV16 / 18 mucosal repair hydrogel, characterized in that, The preparation method of the mucosal repair hydrogel includes the following steps: Step 1: Weigh the raw materials and perform dry heat removal pretreatment; Step 2: Dissolve the highly active chitosan at low temperature, and then remove impurities by 0.22μm ultrafiltration; Step 3: Prepare the polysaccharide matrix by stepwise cross-linking at room temperature; Step 4: Mix the active ingredients with the moisturizing ingredients; Step 5: Precisely adjust the pH of the mixture and mix at a low temperature; Step 6: The low-temperature mixing system is aseptically filtered and filled using ISO5 laminar flow in a graded clean area.

5. The application of a high-polymerization-degree, high-deacetylated chitosan according to claim 4 in an anti-HPV16 / 18 mucosal repair hydrogel, characterized in that, In step one, all raw materials are accurately weighed according to their weight proportions; the solid polysaccharide raw materials are then placed in an electric heating drying oven and dried at 120°C for 30 minutes to remove endotoxins; panthenol, sodium hyaluronate, lactic acid buffer and other liquid excipients are pre-filtered through a 0.45μm PTFE filter membrane for later use; the production equipment is cleaned with water for injection and sterilized with pure steam in advance.

6. The application of a high-polymerization-degree, high-deacetylated chitosan according to claim 4 in an anti-HPV16 / 18 mucosal repair hydrogel, characterized in that, In step two, highly active chitosan is added to 20 to 50 times its weight in sterile purified water to prepare an aqueous solution with a mass fraction of 2% to 5%; the solution is stirred at low temperature and in the dark at 4 to 10°C and 70 to 80 r / min until completely dissolved; and protein impurities are removed by low-temperature circulating filtration using a 0.22 μm ultrafiltration membrane.

7. The application of a high-polymerization-degree, high-deacetylated chitosan according to claim 1 in an anti-HPV16 / 18 mucosal repair hydrogel, characterized in that, The process of preparing the polysaccharide matrix by stepwise cross-linking at room temperature in step three: (1) Add chitosan quaternary ammonium salt to pre-stored sterile purified water and stir at 200-300 r / min to swell for 20-30 min to form a transparent cationic colloid; (2) Add sodium alginate into the system slowly and evenly in 3 to 5 batches, and stir at the same speed for 25 to 35 minutes to allow the anionic and cationic polysaccharides to cross-link and form a three-dimensional sustained-release network framework. (3) After cross-linking, the mixture is sealed and left to stand for 10-15 minutes for vacuum degassing to obtain the polysaccharide matrix.

8. The application of a high-polymerization-degree, high-deacetylated chitosan according to claim 1 in an anti-HPV16 / 18 mucosal repair hydrogel, characterized in that, In step four, the moisturizing components are mixed as follows: chitosan active solution, panthenol, and sodium hyaluronate are added to the polysaccharide matrix in sequence at a uniform speed; the mixture is stirred at a uniform speed of 250-350 r / min for 35-40 min at room temperature.

9. The application of a high-polymerization-degree, high-deacetylation chitosan according to claim 1 in an anti-HPV16 / 18 mucosal repair hydrogel, characterized in that, The precise pH adjustment and low-temperature mixing process in step five: (1) Add lactic acid buffer dropwise under low speed stirring at 100-200 r / min, monitor pH online in real time, and keep it stable at 4.0-5.0; (2) Low temperature mixing: temperature 4~10℃.

10. The application of a high-polymerization-degree, high-deacetylated chitosan according to claim 1 in an anti-HPV16 / 18 mucosal repair hydrogel, characterized in that, The step six involves aseptic filtration in a graded clean area and ISO5 laminar flow filling process. (1) The mixed gel material was filtered through a 0.22μm sterile terminal filter membrane; (2) The filtered material is transferred to a Class B clean production room through a closed pipeline and aseptic filling and sealing are completed in an ISO5 unidirectional laminar flow hood. (3) Monitoring of settling bacteria, airborne bacteria, and surface microorganisms is carried out simultaneously throughout the entire production process; simulated filling of culture medium is performed for each batch; (4) After sealing, the finished product should be stored in a light-proof sealed warehouse at 4-25℃, avoiding high temperature and direct sunlight; The finished product's physicochemical properties are as follows: dynamic viscosity 15000~20000mPa·s; in vitro mucosal adhesion time ≥7h; pH value: 4.0~5.0.